تبلیغی جماعت کے ابتدائی اکابر کا تصوف سے تعلق کا ایک تحقیقی مطالعہ: A RESEARCH STUDY ON THE RELATIONSHIP OF THE EARLY ELDERS OF THE TABLIGHI JAMAAT WITH SUFISM (Al-Aasar, 2026)
This research paper presents a brief scholarly and analytical study of the spiritual conduct and Sufi affiliation of the early elders of the Tablighi Jamaat. The primary objective of this study is to clarify the extent of their connection with Sufism and to examine the degree to which they were associated with Sufi traditions and the discipline of spiritual purification (tazkiyah al-nafs) in their intellectual and spiritual formation.A historical and analytical methodology has been adopted in this study. In the light of biographies, malfuzat (sayings), and other relevant scholarly sources related to the senior figures of the Tablighi movement, their religious and spiritual background has been critically examined. The findings of this research indicate that the elements of sincerity and devotion (ikhlas and lillahiyyah) in their preaching and missionary efforts were strongly influenced by their association with Sufi training (suluk) and the discipline of the tariqah.This study further investigates the nature of the relationship between the early elders of the Tablighi Jamaat and Sufism, the role of Sufi mentors in shaping their intellectual and spiritual development, and the extent to which this relationship influenced their approach to da‘wah (preaching) methodology.